EXPERIENCE OF USING ADVANCED INFORMATION TECHNOLOGIES IN TRAINING FUTURE TRANSLATORS IN UK UNIVERSITIES - E.V. Dolinskyi (Ìнформаційні технології в освіті)
The quality of teaching is not only to use the Internet or e-learning. The novelty of the information and communication technology is to change the orientation of training, the transition to the creation of online and e-learning systems, but also remains an unsolved problem of adaptation of new materials. With IT students develop creativity, independence, professionalism. Interactive technologies provide various kinds of user interaction (sound, images, animations, etc.) and is a basic tool for the creation of computer training programs. The synthesis of traditional and modern information technology is based on the activity- when learning activities are the subject of training and help to create an overview of the professional activities of an interpreter as a purposeful, active, long-term process of learning. Using an interdisciplinary approach makes it possible to seamlessly integrate the knowledge of linguistics and computer science, linguistics and psychology. The purpose of this paper is the analysis of experience in the use of new information technologies in the training of future translators in UK universities. In this research we identified the most common programs used in the preparation of translators, substantiated the possibility of their application, named the city and universities in the UK where such training is carried out.